2003
DOI: 10.1176/appi.ps.54.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Homeless Adults With Mental Illness in a Housing Program and in Case Management Only

Abstract: The results suggest that the effectiveness, and ultimately the cost, of homeless services can be improved by matching the type of service to the consumer's level of psychiatric impairment and substance use rather than by treating mentally ill homeless persons as a homogeneous group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
1
10

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 18 publications
3
66
1
10
Order By: Relevance
“…Drake et al (1997) observed modest, yet significant, decreases in alcohol and drug use after 18 months of follow-up among participants who were placed in housing. 18 In their study of homeless veterans with substance use and/or psychiatric disorders, Clark and Rich (2003) found decreased substance use over a 12-month period, but no differences in level of improvement were found when comparing a comprehensive supportive housing program that included case management to case management alone. 16 In contrast to the previous literature, we observed no significant differences in health status, substance use, health care utilization, or residential stability between the two groups over time resulting from our supportive housing program.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Drake et al (1997) observed modest, yet significant, decreases in alcohol and drug use after 18 months of follow-up among participants who were placed in housing. 18 In their study of homeless veterans with substance use and/or psychiatric disorders, Clark and Rich (2003) found decreased substance use over a 12-month period, but no differences in level of improvement were found when comparing a comprehensive supportive housing program that included case management to case management alone. 16 In contrast to the previous literature, we observed no significant differences in health status, substance use, health care utilization, or residential stability between the two groups over time resulting from our supportive housing program.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research involving homeless and vulnerably housed adults have shown improvements in residential stability and decreases in health care utilization resulting [16][17][18] The effects of supportive housing on substance use are less clear. Drake et al (1997) observed modest, yet significant, decreases in alcohol and drug use after 18 months of follow-up among participants who were placed in housing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ces résultats sont aussi rapportés dans les revues systématiques de Nelson et al (2007) et Rog (2004. Clark et Rich (2003) montrent plutôt que ce sont précisément les personnes ayant des troubles mentaux graves et une forte consommation de substances qui ont bénéficié de l'approche « logement d'abord » sur le plan du logement, alors que celles ayant des troubles plus légers n'en ont pas davantage bénéficié (réf. « résultats mitigés » dans le tableau 8).…”
Section: Comparaison Entre L'approche « Logement D'abord » Et Les Intunclassified
“…Les études qui ont mesuré la santé mentale et la consommation de substances ont plutôt montré que l'approche « logement d'abord » n'a pas davantage d'effets sur ces dimensions que les interventions psychosociales traditionnelles (Clark & Rich, 2003 ;Nelson et al, 2007 ;Padgett et al, 2006). Elle ne permettrait pas non plus de diminuer davantage les visites aux urgences hospitalières (Montgomery et al, 2013).…”
Section: Comparaison Entre L'approche « Logement D'abord » Et Les Intunclassified